FUNCTIONAL GRAMMAR ANALYSIS OF THE NARRATION IN L’ORÉAL’S NEVER YOUR FAULT VIDEO CAMPAIGN (2024) - Azzahrah, Khairunnisa (Language Horizon: Journal of Language Studies, 2025)
This study analyzes the narration in L’Oréal’s Never Your Fault (2024) video campaign using Fontaine’s (2012) Functional Grammar theory, which is rooted in Halliday’s (1994) Systemic Functional Linguistics. The objective of this research is to reveal how linguistic choices in the campaign’s narration represent women’s identity, the discourse of victim-blaming, and women’s empowerment. Employing a qualitative method, the data were taken from the narration script and examined through three metafunctions: ideational, interpersonal, and textual. The findings indicate that women’s identities are primarily represented through mental and material processes, highlighting how women often internalize self-blame in cases of street harassment. Conversely, men are depicted through material and behavioral processes, portraying them as active agents of harassment. From the interpersonal perspective, the narration employs declarative sentences to illustrate women’s vulnerability and imperative sentences to provide authority, empowerment, and collective calls to resist victim-blaming. Textually, the narration builds coherence through repetition and thematic development, such as the recurring patterns of “She thinks...” and “Don’t blame...,” which create rhythm and emotional resonance. Overall, the analysis demonstrates that L’Oréal positions itself as an advocate for women’s empowerment while challenging entrenched cultural norms of victim-blaming.